Comparative Study of the Relationship between Spiritual Well-being and Sense of Coherence in Mothers with Chronically Ill Children in Kerman, Iran, in 2016 - Nosrat Avaznejad; Maryam Ravanipour; Niloofar Motamed; Masoud Bahreini (Mashhad University of Medical Sciences, 2017)
This study aimed to investigate the relationship between spiritual well-being and sense of coherence in the mothers having children with chronic diseases. To this end, a controlled cross-sectional evaluation was conducted on 300 mothers, divided into two groups of 150 cases with healthy and chronically ill children in the city of Kerman, Iran, in 2016. The data were collected using the Platosin and Alison's Spiritual Wellbeing Scale and Atonovesky's Sense of Coherence Scale. The mean ages of the mothers with healthy children and those with chronically ill children were 36.1±4.6 and 37.7±6.2 years, respectively. The linear regression analysis showed that by controlling the effect of the groups (i.e., the mother with a healthy or chronically ill child), the spiritual well-being score had a significant impact on the sense of coherence (P=0.001). It was concluded that the promotion of spiritual well-being, especially existential well-being, could potentially develop the sense of coherence in the mothers with chronically ill children by helping them better control the diseases of their children.